Spirulina Production in a Controlled Environment in Niger - Naroua Koure Mamane Kabirou; Halima Oumarou Diadie; Roukaya Abdou Souley; Rabiou Abdou Abdoul Rachid; Balla Abdourahamane (European Scientific Journal, ESJ, 2026)
Spirulina, an excellent dietary supplement, is an alga very rich in proteins, vitamins and minerals. The cultivation of spirulina requires optimum control of culture parameters (Temperature, pH, Salinity, Lighting) which are most often lower than the optimal production conditions. The objective of this study is to optimize the production of spirulina. To do this, a randomized experimental design was carried out in a greenhouse to control the effect of light and temperature. A total of nine (9) treatments repeated three (3) times were conducted in the greenhouse. The culture media of the different treatments used were composed of natron, salt, NPK fertilizer, urea, lime, iron and ash water. These media are mainly distinguished by the chemical composition linked to the quantitative variation of the inputs used. Thus, the culture parameters (pH, temperature, salinity and density of the culture medium) were recorded. The yield obtained during the experiments was also evaluated. The results from these tests show that there is a great variability in the culture parameters depending on the type of treatment used. Thus, the pH and salinity of the medium fluctuate respectively between 8.95 and 10.16 and 16g/l and 31g/l. The average temperature of the medium varies between 28.32°C ± 0.72 (n = 189) in the morning and 34.06°C ± 1.71 (n = 189) in the evening. For the daily growth values ​​noted in the media, T1 (control) shows a greater growth from the first (1st) day to the third (3rd) day, with a peak μ = 0.66. On the other hand, this growth becomes relatively low until the seventh (5th) day of the test. However, treatments T4, T5, T6 and T8 showed a more or less linear growth from the first (1st) to the seventh (7th) day of the test. The result indicated an optimal yield of 1.13g/l± 0.13 with treatment T6, which was significantly higher than the yields of the other treatments. However, the lowest yield (0.46g/l±0.08) was observed with treatment T3.